A dyslexia-friendly classroom: can this make lessons more inclusive for Kai? - Kempson, Susannah (2012)
All children have the right to equal opportunities Armstrong, Armstrong and Barton, 2000). A dyslexia-friendly classroom has been suggested to provide beneficial learning opportunities for all children (MacKay and Tresman, 2005; Pavey, 2007). This research used the dyslexia-friendly approach over six lessons to discover if it would make lessons more inclusive for an eight-year old boy with pathological demand avoidance syndrome (PDA). The lessons were investigated through interviews with the adults who supported the boy and questions to all children in the class about their views on the lessons. It was found that dyslexia-friendly lessons seemed to be beneficial for the boy with PDA. Also it appeared to be beneficial for other children. The research suggests that multisensory and personalised learning should be used as a teaching tool, and that distractions when learning should be avoided. It is also argued that although group work is beneficial for those with special educational needs (SEN), one-to-one learning is equally important both in and outside the classroom.